The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/nu12113563
|View full text |Cite
|
Sign up to set email alerts
|

Prisoners of Addictive Cues: Biobehavioral Markers of Overweight and Obese Adults with Food Addiction

Abstract: Obesity is associated with food and eating addiction (FA), but the biobehavioral markers of this condition are poorly understood. To characterize FA, we recruited 18 healthy controls and overweight/obese adults with (n = 31) and without (n = 17) FA (H-C, FAOB, NFAOB, respectively) to assess alpha brain asymmetry at rest using electroencephalogram; event-related potentials following exposure to high-calorie food (HCF), low-calorie food (LCF), and nonfood (NF) images in a Stroop paradigm; reaction time reflectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 111 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that monetary rewards may lead to a significant decline in the cost of inhibition control and switching [46]. For this reason, overweight people should allocate more cognitive resources to inhibiting food cravings [22,42]. Overall, these findings suggest that the mediating effect of food cravings on the indicators of overweight and the switching process is related to the distribution of attention and cognitive resources.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Previous studies have shown that monetary rewards may lead to a significant decline in the cost of inhibition control and switching [46]. For this reason, overweight people should allocate more cognitive resources to inhibiting food cravings [22,42]. Overall, these findings suggest that the mediating effect of food cravings on the indicators of overweight and the switching process is related to the distribution of attention and cognitive resources.…”
Section: Discussionmentioning
confidence: 63%
“…This result verifies Hypothesis 2. Overweight individuals tended to have higher food cravings [42] and showed an approach-avoidance pattern of attention allocation toward high-energy food [43], resulting in impaired performance in the switching tasks with food stimulation. Food-related attentional bias is sensitive to changes in the motivational and rewarding value of food [44].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, late-stage motivated attention as reflected by enlarged P300 and LPP amplitudes occurred more consistently ( Ceballos et al, 2012 , Delgado-Rodríguez et al, 2019 , Herrmann et al, 2001 , Kim et al, 2018 , Kroczek et al, 2018 , Namkoong et al, 2004 , Petit et al, 2013 , Petit et al, 2014 , Petit et al, 2015 , Schienle et al, 2017 , Svaldi et al, 2010 , Thalemann et al,2007 , Wölfling et al, 2011 ). One study on pathological internet use ( Lai et al, 2017 ), three on binge eating ( Aviram-Friedman et al, 2020 , Lutz et al, 2021 , Wolz et al, 2017 ) and two on binge drinking ( Petit et al, 2012 , Ryerson et al, 2017 ) brought forth no significant or only very limited effects on P300 or LPP. As found in most studies, an increase in later ERP amplitudes to relevant cues in populations of different binge behaviors is in line with a common incentive sensitization process.…”
Section: Discussionmentioning
confidence: 99%
“…However, negative mood induced a stronger LPP amplitude enhancement in high calorie food for this BN sample ( Lutz et al, 2021 ). Though, an overweight sample with food addiction displayed a lower LPP amplitude change (between 450 and 495 ms) following high calorie food pictures compared to neutral pictures, compared to an overweight sample without food addiction for frontal and right posterior electrodes ( Aviram-Friedman, Kafri, Baz, Alyagon, & Zangen, 2020 ).…”
Section: Binge Eatingmentioning
confidence: 93%